Sand Mining in Uganda: Strengthening the Legal Framework to Combat Corruption and Environmental Destruction and Attract Better Foreign Investment. - Zoe Richard Mauki (KAS African Law Study Library)
Investment is vital in stirring the country’s economy and sustaining development, especially in Africa and Uganda. It also serves as a tool for technology transfer, innovation, employment, and generating revenue for individuals and the government. This article focuses on sand mining in Uganda, the level of corruption involved, the lack of a proper legal framework to govern its exploitation, and the investors’ interest in the sector. Uganda is rich in copper, gold, iron, and ore minerals. Others include sand, hardcore, gravels, aggregates, and local granite. Article 244 of the Uganda Constitution 1995 provides that ‘building substances such as clay, murram, sand or any stone commonly used for building’ are not regarded as minerals. However, the parliament hardly enacted legislation to govern these excluded minerals. Currently, this is an area that is attracting foreign investment. At the same time, it is unregulated. The paper will discuss, among others, the importance of having a proper legal framework to regulate building materials such as sand, why it is important, and how the lack of a proper legal framework to govern the sector might cost the government of Uganda sums of money.